THE IMPACT OF COVID-19 ON TRADE VOLUME AND STOCK PRICE MOVEMENTS OF SOES IN THE CONSTRUCTION SECTOR - Martiani Tambunan; Rahmadianti Thomas (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The condition of Indonesia, which is currently being hit by the Covid-19 pandemic, is affecting the stock market and economic growth. One of the events that allegedly caused changes in prices and trading volume in 2020 was the Covid-19 pandemic, which not only hit the global stock market but also in Indonesia. The economic turmoil caused by the Covid-19 pandemic has hit Indonesia with the least impact in various sectors. A possible risk that investors and capital market analysts worry about is a recession and an economic crisis due to an economic slowdown. The Composite Stock Price Index (IHSG) experienced a decline, especially in the construction sector. The research method used in this research is quantitative research. Data collected in the form of secondary data from the IDX. This method uses a different test analysis model test t-test. The sample in this study consisted of 4 stocks, namely BUMN shares which were included in the construction stock sector, namely: Adhi Karya (Persero) Tbk, PP (Persero) Tbk, Wijaya Karya (Persero) Tbk, and Waskita Karya (Persero) Tbk. The variable used is the volume of stock prices before and after Covid-19. The Covid-19 pandemic in Indonesia affected the capital market and caused changes in trading times on the Indonesia Stock Exchange.